Amount of Frictional Force of Steel Rope Against The Bollard Due To The Loading In The Process of Towing Lorry at PT. XYZ - Darmadi, Herry; Irwansyah, Irwansyah; Kurnia, Dian; Hidayat, Rendy Ardian (Jurnal Sains dan Teknik Terapan, 2024)
Bollard is a piece of equipment found at the fruit receiving station which has the working principle of turning the steel wire rope and holding it in the process of pulling the lorry to be put into the sterilizer, to move the lorry to each door, the loading ramp is pulled by a capstand using a steel wire rope attached to it. to the bollard as a support and deflector so that the lorry can move forward and backward. The event that occurs as a result of pulling a lorry using a sling is an event where friction forces occur, and the friction that occurs on the bollard is caused by the presence of two objects in contact with a normal load. In this study, the value of the friction force that occurs on the steel wire rope against the bollard is calculated. From the research results, it was concluded that the amount of frictional force that occurs on the steel wire rope against the bollard when under load is influenced by the capstand speed which is quite low due to the load condition of 173,850 kg m/s². Meanwhile, the magnitude of the frictional force that occurs in the steel wire rope against the bollard under no-load conditions is influenced by the faster pulling speed, so the friction force value is 116,850 kg m/s²